2023
DOI: 10.1186/s12870-023-04429-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing hydrothermal time models to assess the effects of temperature and osmotic stress on maize (Zea mays L.) germination and physiological responses

Waqif Khan,
Sumbal Shah,
Abd Ullah
et al.

Abstract: The application of germination models in economic crop management makes them extremely useful for predicting seed germination. Hence, we examined the effect of varying water potentials (Ψs; 0. − 0.3, − 0.6, − 0.9, − 1.2 MPa) and temperatures (Ts; 20, 25, 30, 35, 40 °C) on maize germination and enzymatic antioxidant mechanism. We observed that varying Ts and Ψs significantly influenced germination percentage (GP) and germination rate (GR), and other germination parameters, including germination rate index (GRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The probable explanation is that suitable temperatures facilitate water uptake by the seed, enhance enzymatic processes and respiration, and store nutrients in a soluble state that is easy to use [ 69 ]. Understanding the response of plants to temperature not only helps us to understand their ecological adaptations, but also helps in developing effective vegetation restoration strategies [ 70 ]. This study’s findings on the species-specific responses of seed germination to temperature are in line with other research, as various species have different optimal temperatures and temperature ranges [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The probable explanation is that suitable temperatures facilitate water uptake by the seed, enhance enzymatic processes and respiration, and store nutrients in a soluble state that is easy to use [ 69 ]. Understanding the response of plants to temperature not only helps us to understand their ecological adaptations, but also helps in developing effective vegetation restoration strategies [ 70 ]. This study’s findings on the species-specific responses of seed germination to temperature are in line with other research, as various species have different optimal temperatures and temperature ranges [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different temperature and water potential conditions can affect seed germination through changes in seed composition, including seed oil and carbohydrates [6]. It has been reported that Bidens pilosa L. (Asteraceae) [7] and maize (Zea mays L.) [8] seed populations had different germination responses to temperature and water potential, and the optimal and ceiling temperatures were varied.…”
Section: Introductionmentioning
confidence: 99%